Meta-Analysis: Effects of Smoking, Alcohol Consumption, and Low Physical Activity on Osteoporosis in Adults - Muhammad Fahrezi Al Ghifari; Yulia Himawati; Aem Ismail; Bhisma Murti (Journal of Epidemiology and Public Health, 2024)
Background: Osteoporosis is a systemic skeletal disease characterized by low mineral bone mass and microarchitectural deterioration of bone tissue. This study aims to analyze the effect of smoking, alcohol consumption, and low physical activity on osteoporosis in adults.Subjects and Method: This was a meta-analysis study using the PICO format. Population: Adults, Intervention: Smoking, Alcohol Consumption, Low Physical Activity, Comparison: No Smoking, No Alcohol Consumption, High Physical Activity, Outcome: Osteoporosis. Articles were searched using online databases such as PubMed, Google Scholar, Science Direct. The search for articles using the keywords "Smoking" OR "Tobacco" AND "Alcohol consumption" OR "Drinking" AND "Physical activity" OR "Exercise" AND "Osteoporosis" OR "Bone mineral density" AND "Cross-sectional". The inclusion criteria for articles used were articles published in 2013-2023. Articles were filtered using PRISMA flow diagrams and analysis was conducted using RevMan 5.4.Results: The meta-analysis used 15 articles with cross-sectional studies from Ireland, Nepal, Taiwan, South Korea, China, Iran, America, Brazil, India, Congo, and Thailand with a total sample of 111,478 samples. The risk of osteoporosis increased with smoking (aOR= 1.49; CI 95%= 1.04 to 2.16; p= 0.030), alcohol consumption (aOR= 1.04; CI 95%= 0.84 to 1.30; p = 0.690), and low physical activity (aOR= 1.17; CI 95%= 0.92 to 1.48; p= 0.210).Conclusion: Smoking, alcohol consumption, and low physical activity increase the risk of osteoporosis in adults. Keywords: smoking, alcohol consumption, physical inactivity, osteoporosis.